Individual well-being and national determinants of screening mammography among women over fifty - Boaz Hovav; Shuli Brammli-Greenberg (International Journal for Equity in Health)
Abstract Background Breast cancer is the most prevalent cancer among women worldwide, causing over 400,000 cases of premature death annually. Timely screening mammography (SM) could have prevented most death. Although SM utilization varies across countries, few studies have examined country-level factors, and fewer explored their interaction with individual-level factors. The study aims to analyze individual and country-level variables and their interaction that determines SM utilization and variation between countries. Methods Individual, country, and cross-level models are used to analyze the cross-sectional data from the SHARE database for 26,672 women aged 50 or over, from 27 countries. Key individual variables investigated include quality-of-life (QOL), psychological, and subjective-health status. Country-level variable included government health expenditure (GHE) percentage of GDP, and organized screening programs. Models were adjusted for individual variables such as age and education. Results Self-reported SM utilization varied from 5 to 67% in the countries examined. On the individual level, higher QOL, psychological, and subjective health status positively correlated with SM utilization, as did GHE and organized programs on the country-level. Surprisingly, the interaction between individual and country-level variables shows that while SM utilization positively correlates with higher psychological and subjective health status in high-GHE countries, it negatively correlates in low-GHE countries, and only weakly positive correlates in mid-level GHE countries. Conclusions Better individual well-being, both physical and psychological, increased SM utilization, as did higher GHE and countrywide SM programs. The negative correlations in low-GHE countries and positive correlations in high-GHE countries underscores disparities that need to be addressed.